Paecilomyces variotii as A Plant-Growth Promoter in Horticulture - Alejandro Moreno-Gavíra; Fernando Diánez; Brenda Sánchez-Montesinos; Mila Santos (Agronomy, 2020)
In the present study, P. variotii, an endophytic fungus isolated from plant roots from the Cabo de Gata Natural Park (Parque Nacional Cabo de Gata—Spain), was tested to determine the effect on the growth promotion of tomato and pepper seeds and seedlings. For these purposes, germination trials in a laboratory and two experiments in a commercial nursery and greenhouse conditions were performed. The P. variotii isolate has shown a high ability to produce siderophores and IAA, but low ability to solubilize P. High values for germination percentage, seedling vigor, root and shoot length were obtained by P. variotii on tomato and pepper against control. P. variotii applications resulted in improved most of the growth parameters evaluated, for both horticultural crops, with the best results in the development of pepper seedlings. The application of a higher dose of P. variotii improved most of the morphological parameters and the Dickson quality index (DQI) value in tomato in seedlings and plants. The establishment of the endophytic fungus at the root enabled its biostimulant effects to persist after transplantation without any additional application. Few studies have analyzed this species as a biostimulant. The positive results from the tests showed its high potential. The application of this isolate can be of enormous benefit to horticultural crops for its high reproductive and establishment capacity.